Contributions of good teaching practices for teacher improvement in higher education - Carlos-Guzmán , Jesus Jose (Education Policy Analysis Archives, 2021)
Interested in improving the quality of teaching in Higher Education Institutions (IES), we integrate research on good teachers, carried out by both the author and other researchers. These studies are distinguished by having used different methodologies, being carried out at different times and in different places; however, there are important coincidences. The results were grouped into five categories that distinguish good teachers: 1) their didactic ability and mastery of the subjects taught, 2) have adequate interpersonal relationships with students, 3) the importance they give to their work, 4) possess certain visions and beliefs about teaching and 5) the motivation, commitment and responsibility with which they carry out their role. We use the results to base an educational policy that educational institutions could apply for: the selection of new teachers, the promotion and appreciation of good teaching, as well as the criteria for teacher evaluation, incentive programs academic productivity and for teacher training. We hope that what is proposed contributes to making good teaching a common practice in educational institutions and not just an isolated result of personal motivations and commitments.